Confocal Microscopy. Issue 7 (15th October 2008) - Carter, David
Abstract: This overview covers the two main types of confocal scanner. Point scanners are more flexible and give the best resolution, while camera‐based systems can be more sensitive, faster, and more automated. The procedure for setting up and using these instruments is described in sufficient depth for basic operation. Beyond collecting single images, a Z ‐series, which captures a volume of data, a kinetics series, collecting a sequence of images, and generation of a large montage image are all described. Confocal is an extension of regular fluorescence microscopy, with the ability to handle thicker and more heavily stained specimens and to work more precisely with physiological markers in live samples and organelle stains. Such techniques are highly divergent, depending on specimen type, so they cannot be covered in any detail here, but a general idea will give the user confidence to explore the literature and collect good data on their own systems. Curr. Protoc. Essential Lab. Tech . 7:9.4.1‐9.4.36. © 2013 by John Wiley & Sons, Inc.